One- and two-triplon spectra of a cuprate ladder - Schmidt, Kai Phillip; et al. (Physical Review Letters, 2007)
We have performed inelastic neutron scattering on the near ideal spin-ladder compound La4Sr10Cu24O41 as a starting point for investigating doped ladders and their tendency toward superconductivity. A key feature was the separation of one-triplon and two-triplon scattering. Two-triplon scattering is observed quantitatively for the first time and so access is realized to the important strong magnetic quantum fluctuations. The spin gap is found to be 26.4 +/- 0.3 meV. The data are successfully modeled using the continuous unitary transformation method, and the exchange constants are determined by fitting to be J(leg) = 186 meV and J(rung) = 124 meV along the leg and rung, respectively; a substantial cyclic exchange of J(cyc) = 31 meV is confirmed.